2008
DOI: 10.1152/japplphysiol.90456.2008
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory feedback from the limbs exerts inhibitory influences on central neural drive during whole body endurance exercise

Abstract: We investigated whether somatosensory feedback from contracting limb muscles exerts an inhibitory influence on the determination of central command during closed-loop cycling exercise in which the subject voluntarily determines his second-by-second central motor drive. Eight trained cyclists performed two 5-km time trials either without (5K(Ctrl)) or with lumbar epidural anesthesia (5K(Epi); 24 ml of 0.5% lidocaine, vertebral interspace L(3)-L(4)). Percent voluntary quadriceps muscle activation was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 79 publications
5
133
1
Order By: Relevance
“…Further indirect indices of a higher central motor drive are provided by the greater central cardiovascular and respiratory responses during double-leg KE ( Figs. 1 and 2), both of which are determined by feedback and feedforward mechanisms (8). In the presence of greater central motor drive, less overall afferent feedback from the exercising limbs would be required to reach the sensory tolerance limit during doubleleg KE.…”
Section: Discussionmentioning
confidence: 99%
“…Further indirect indices of a higher central motor drive are provided by the greater central cardiovascular and respiratory responses during double-leg KE ( Figs. 1 and 2), both of which are determined by feedback and feedforward mechanisms (8). In the presence of greater central motor drive, less overall afferent feedback from the exercising limbs would be required to reach the sensory tolerance limit during doubleleg KE.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas blockade of neural feedback from working muscles with epidural anesthesia does not impair hypoxia-induced increases in systemic cardiovascular and neuroendocrine responses (57), evaluation of the central motor drive during hypoxic exercise when manipulating muscle afferent signals is needed to confirm their impact on the CNS in hypoxic conditions. This should include selective blockade of ascending sensory pathways and avoid the confounding effect of motor nerve activity or maximal force output impairments (10,11,57).…”
Section: Afferent Signals From Working Musclesmentioning
confidence: 99%
“…In addition, comparison of the O2 associated with the initial stage of each constant RPE ride indicated that subjects maintained a higher O2 cost (p < 0.01; d = 0.67) during the first 20 min of rides at RPEGET+15% than those at RPEGET. There was no significant difference between RPEGET and RPEGET+15% for O2 at min [21][22][23][24][25][26][27][28][29][30][31][32][33] …”
Section: Resultsmentioning
confidence: 99%
“…These findings were consistent with those of Cochrane et al [6] who reported a close agreement between RPE and , but dissociations for both RPE and vs. metabolic ( O2 and RER), cardiovascular (HR), and ventilatory ( E) responses during constant RPE cycle ergometry within the moderate intensity domain. It was hypothesized [6] that reflex actions associated with the exercise pressor reflex model of fatigue [12,[29][30][31] best explained the similarity for RPE and during the constant RPE rides. According to the exercise pressor reflex model [12,[29][30][31], afferent signals from small group III (mechanical changes) and IV afferents (metabolic changes) from working thigh and respiratory muscles mediate the ventilatory, cardiovascular, and RPE responses during moderate and heavy intensity exercise [2,12,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation